2004
DOI: 10.1023/b:popu.0000034097.35915.e1
|View full text |Cite
|
Sign up to set email alerts
|

Naturalization of U.S. Immigrants: Highlights from Ten Countries

Abstract: The saga of U.S. immigrant naturalization is merely sketched for about 25 million immigrants entered in three decades of renewed immigration. This study documents naturalization outcomes for immigrants from ten major countries of origin, using administrative records on immigrants and naturalizations. Following the 1978-1987 admission cohorts for the first decade or more of permanent residence, this study finds significant covariate effects on the timing of naturalization by origin, mode of entry, and immigrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Conversely, the probability of not wanting to naturalise increases with age. This result, in line with the existing literature (Woodrow-Lafield et al 2004;Kahanec and Tosun 2009;Devoretz 2008), is not surprising: compared to the elderly, younger people have more to gain from citizenship. The younger are more likely to be economically active and have jobs for which citizenship is required or at least advantageous, they are more willing to travel abroad and more likely to seek participation in the political processes of the country and, arguably, they are more likely to accept the whole idea of naturalisation.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Conversely, the probability of not wanting to naturalise increases with age. This result, in line with the existing literature (Woodrow-Lafield et al 2004;Kahanec and Tosun 2009;Devoretz 2008), is not surprising: compared to the elderly, younger people have more to gain from citizenship. The younger are more likely to be economically active and have jobs for which citizenship is required or at least advantageous, they are more willing to travel abroad and more likely to seek participation in the political processes of the country and, arguably, they are more likely to accept the whole idea of naturalisation.…”
Section: Resultssupporting
confidence: 80%
“…This paper studies the costs and benefits of acquiring Latvian citizenship accruing to non-citizens, as well as the obstacles standing in the way, and determines what individual and municipality level factors affect the willingness and/or reluctance to naturalise. 4 Following the literature (Bratsberg et al 2002;Devoretz and Pivnenko 2005;Devoretz 2008;Garcia 1981;Kahanec and Tosun 2009;Woodrow-Lafield et al 2004;Zimmermann et al 2009;Yang 1994), we view the decision to ascend to citizenship within a cost-benefit framework and recognise the role of social, economic and demographic factors, ethnic networks, and regional, institutional and attitudinal effects in the decision to naturalise. This paper makes several important contributions to the burgeoning theoretical and empirical literature on citizenship acquisition (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion above suggests the possible importance of macro-level or contextual factors such as community composition and political institutions in the country of origin and in the U.S. Few studies (such as Bueker 2006, Yang 1994, Woodrow-Lafield et al 2004, and Liang 1994) have studied these questions for multiple ethnic/racial groups. Our approach is to pool together immigrants from all backgrounds in order to estimate a general model of naturalization that includes both individual and contextual factors.…”
Section: Methodsmentioning
confidence: 99%
“…1 Only through the use of administrative records would it be possible to identify legal immigrants and track their progress toward naturalization (as in the research by Woodrow-Lafield et al 2004). We address this limitation by including for the first time in a study of naturalization an occupation measure that has been found to be strongly associated with legal status (Passel and Clark 1998; see also Kooudji and Cobb-Clark 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation